HOW TO WRITE A GOOD ARTICLE FOR PUBLICATION IN TERRA NOVA. (13th November 2018) - Braun, Jean; Coleman, Max; Morgan, Jason Phipps; Doglioni, Carlo; Calas, Georges; Mezger, Klaus
Abstract : Although as Editors of Terra Nova we receive many well‐written papers, occasionally some submissions are not as good as they could be in all aspects. Therefore, we have put together this guide on what we consider to be a well‐written article for our journal. It may be particularly useful for younger and less experienced authors but even those who have written many papers may find some parts of this to be useful. However, please note that this is not a prescription for writing a paper acceptable to Terra Nova . If in your writing you have other ways of achieving the same objectives described below, we shall go on welcoming the diverse range of submissions to Terra Nova .